High-Risk Factors causing Mortality in Pediatric Burn Patients, admitted in Burns Centre of Karachi - Lubna Riaz, Riaz Ahmed Shahid, Muhammad Noman Rashid, Roomana Batool, Saleem Ullah Abro, Qurratulain Saleem (Journal of Rawalpindi Medical College, 2021)
ABSTRACT Background: Different risk variables that lead to mortality of a burn victim. The most important categories for assessment of severity in burns among pediatric age group is, total body surface area (TBSA) involved, age and type of burn which can lead to increased deaths. The current study was performed to analyze the various factors of causing risk of burns and leading to mortality. Methods: It is a cross-sectional non-probability descriptive study, performed of Pediatric Burns unit Ruth Pfau Civil hospital, Karachi. Clinical recordof 227 Patients of both sexes135 males and 92 females was analyzed after receiving approval from Burn Center, Ruth Pfau Civil Hospital Karachi. Statistical analyzes was carried out using version 20.00 of SPSS. Results: Largest percentage of mortality was in age between 1 and 5 years. In 139 patients, Scalding due to hot water was the most common form of burn. Major cause of mortality was due to multiple burns with > 50% involvement of TBSA was the most common category constituting 68.7% among the patients in the current study. Significant association was analyzed between the nutritional status of patients as assessed by albumin levels and mortality (p=0.004). However, total mortality among the reported cases in between 2016 until 2018 was 28.2% being in 1-5years of age with above-mentioned associations. Conclusion: Current research indicates that an increasing mortality in pediatric burn patients is linked with the proportion of total body surface area (TBSA) exposed to burns, duration of the exposure, decrease total protein content due to damage of tissues and muscles. This leads to prolonged protein and intravenous fluid replacement. One of the most common complication is progression to respiratory failure. Keywords: Burns, burns etiology, burns mortality rate.